2009
DOI: 10.1128/aem.01998-08
|View full text |Cite
|
Sign up to set email alerts
|

Cydia pomonella granulovirus Genotypes Overcome Virus Resistance in the Codling Moth and Improve Virus Efficiency by Selection against Resistant Hosts

Abstract: Cydia pomonella granulovirus (CpGV) has been used for 15 years as a bioinsecticide in codling moth (Cydia pomonella) control. In 2004, some insect populations with low susceptibility to the virus were detected for the first time in southeast France. RGV, a laboratory colony of codling moths resistant to the CpGV-M isolate used in the field, was established with collection of resistant insects in the field followed by an introgression of the resistant trait into a susceptible colony (Sv). The resistance level (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 30 publications
4
117
1
1
Order By: Relevance
“…First, with regard to inheritance and susceptibility to CpGV-M and CpGV-S, populations 1 to 4 (BW-FN, BW-HI, BW-HA, and HE-WI) showed similar patterns of resistance, as previously reported for CpRR1. Most resistant CM field populations in Europe were expected to follow the CpRR1 type of resistance, since resistance in these populations is sex-linked and dominant and can be broken by CpGV isolates lacking the 24-bp insertion in pe38 (4,14,19,26). Only two families, K1f and R27f, deviated from this model, since zero mortality was observed in CpGV-M infections after 7 days, which is not in accordance with Z-linked inheritance.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…First, with regard to inheritance and susceptibility to CpGV-M and CpGV-S, populations 1 to 4 (BW-FN, BW-HI, BW-HA, and HE-WI) showed similar patterns of resistance, as previously reported for CpRR1. Most resistant CM field populations in Europe were expected to follow the CpRR1 type of resistance, since resistance in these populations is sex-linked and dominant and can be broken by CpGV isolates lacking the 24-bp insertion in pe38 (4,14,19,26). Only two families, K1f and R27f, deviated from this model, since zero mortality was observed in CpGV-M infections after 7 days, which is not in accordance with Z-linked inheritance.…”
Section: Discussionmentioning
confidence: 75%
“…For CpRR1, systemic resistance in all instars was observed, and an early block in virus replication was found to be inherited in an incompletely dominant monogenic mode linked to the Z chromosome (13,19,20). It was further found that CpGV resistance had developed only against the commercially used CpGV-M (genome group A), whereas other CpGVs from genome groups B to E were able to break resistance (4,14,21,22). Strikingly, the genomes of all resistance-breaking CpGVs of genome groups B to E had only a single common difference from CpGV-M, which was the insertion of a 24-bp repeat motif in the open reading frame (ORF) pe38 of CpGV-M (4).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The CpGV resistance is mediated by a major gene with concentration-dependent dominance linked to the Z chromosome (26). Although other CpGV isolates were shown to overcome CpGV resistance (27,28) caused by an early blockage of virus replication (29), its genetic basis remains elusive possibly due to false assumption of conserved gene content of the Z chromosome between B. mori and C. pomonella.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, baculoviruses consist of mixtures of different genotypes of the same species and it has been shown that this diversity is naturally favored in wild type virus populations (Clavijo et al, 2011) where these genomic variants are known to impact virulence in the target organism (López-Ferber, 2003;Simón et al, 2008). The different viral genotypes may compensate for variations that occur in the larval host and/or its environment (Berling et al, 2009;Hitchman et al, 2007;Hodgson et al, 2002). For this reason, the evaluation of baculoviruses should be carried out at the species level rather than at the level of a single isolated genotype (Hauschild et al, 2011).…”
Section: Identity Of Baculovirus Productsmentioning
confidence: 99%